Cover Picture: DNA‐Scaffolded Multivalent Ligands to Modulate Cell Function (ChemBioChem 9/2014). Issue 9 (16th June 2014) - Zhang, Zhiqing; Eckert, Mark A.; Ali, M. Monsur; Liu, Linan; Kang, Dong‐Ku; Chang, Elizabeth; Pone, Egest J.; Sender, Leonard S.; Fruman, David A.; Zhao, Weian
<x xml:space="preserve">Abstract</x> The cover picture shows the concept of using DNA‐scaffolded multivalent ligands to modulate cell signaling and function, as reported by W. Zhao, et al. on p. 1268 ff. The multivalent ligand is made of a polymeric DNA scaffold that was synthesized by rolling circle amplification; biorecognition ligands (i.e., antibodies) are attached to this. This multivalent DNA material approach represents a new chemical biology tool for interrogating cell receptor signaling and functions and, potentially, for manipulating such functions for the development of therapeutics.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>